The method of determining the parameters of the soil prism formed in front of the dump during digging - Shevchenko, V.; Olieinikova, O.; Ragulin, V.; Шевченко, Валерій Олександрович; Олєйнікова, Олександра Михайлівна; Рагулін, Віталій Миколайович (Харківський національний автомобільно-дорожній університет, 2023)
The studied dynamic process of digging, taking into account the variable total moving mass of wheeled ZTM equipped with a dump, is not sufficient for the development of recommendations for selecting rational parameters for the performance of such a technological operation. The issue of determining and analyzing the parameters of the variable mass and volume of the material prism moved by the dumper has not been sufficiently investigated. There in no engineering technique that allows you to determine the parameters of the material prism that is gradually forming before dumping. Methodology. The measures are aimed at determining the parameters of the soil prism before the dump in the digging process using analytical dependencies. Results. For the processes of development and analysis of dynamic models of machines with a shovel working body for the stages of digging and transportation of material, it is necessary to take into account its mass in the form of mass attached to the mass of the machine itself. Originality. The obtained dependencies allow to take into account the variable mass of the attached material when performing the analysis of the bulldozer movement in the process of digging the environment being developed. Practical value. The obtained results can be recommended when studying the disciplines of industrial mechanical engineering.
Метод визначення параметрів призми ґрунту, яка формується перед відвалом під час копання
Keywords: bulldozer; prism; dump; dynamic process; technological operation; бульдозер; призма ґрунту; відвал; динамічний процес; технологічна операція; 621.872; 10.30977/AT.2219-8342.2023.53.0.03